The early fossil record of Caturoidea (Halecomorphi: Amiiformes): biogeographic implications - López Arbarello, Adriana (2023)
Caturoidea is a clade of Mesozoic predatory ray-finned fishes which lived mainly in the Jurassic. The clade has a few records in the earliest Cretaceous and only two in the Triassic. Among the latter, specimen MPCA 632 Caturus sp. doubtfully from continental Early Triassic of Argentina, i.e., outside Europe, was particularly problematic in the light of the known fossil record of the group, which suggested their origin in the Western Tethys. The micropaleontological and geochemical analysis of bulk-rock samples of MPCA 632 allowed us to correct the provenance of the specimenwhich corresponds to Tithonian marine outcrops of the Vaca Muerta Formation, Neuquén, Argentina. Specimen MPCA 632 is excluded from Caturus and reclassified as Caturoidea sp. MPCA 632 might be a specimen of Catutoichthys olsacheri, the only caturoid known from the Vaca Muerta Formation (Los Catutos Member), but the fossils are not comparable and, thus, this hypothesis needs further study. Additionally, the first-hand study of the type material of the only other alleged Triassic caturoid, Furo insignis, in the Norian of Seefeld, Austria, led to the exclusion of this taxon from the Caturoidea. Consequently, the clade Caturoidea is restricted to the Jurassic–Lowest Cretaceous. After a modest evolution during the Early Jurassic, the group had its initial radiation and westward dispersionacross the Hispanic Corridor during the Middle Jurassic and reached its maximal diversity during the Kimmeridgian and Tithonian.